Fetuin A is a Predictor of Liver Fat in Preoperative Patients with Nonalcoholic Fatty Liver Disease. (2nd September 2016) - von Loeffelholz, C.; Horn, P.; Birkenfeld, A.L.; Claus, R.A.; Metzing, B.U.; Döcke, S.; Jahreis, G.; Heller, R.; Hoppe, S.; Stockmann, M.; Lock, J.F.; Rieger, A.; et al.
ABSTRACT: Background : Nonalcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) are frequent comorbidities in perioperative patients. However, the predictive role of the hepatokine fetuin A was not evaluated in this collective. Objective : To study fetuin A as predictor of NAFLD/NASH in preoperative patients. Methods : 58 subjects were included. Fetuin A was studied in patients undergoing open abdominal surgery and in a subset with acute liver failure. Blood and liver specimens were sampled. NAFLD was histologically evaluated. Liver fat was additionally analyzed by an enzymatic approach, circulating fetuin A by enzyme linked-immunosorbent assay, fetuin A mRNA by reverse-transcription PCR. Results : Univariate correlation studies linked fetuin A to liver steatosis ( r = 0.40, p = .029) and hepatocellular ballooning degeneration ( r = 0.34, p = .026). Compared to non-NAFLD subjects fetuin A was increased in NAFLD ( p = .009) and in NASH ( p = .029). However, when corrected for main confounders by linear modeling, fetuin A remained related to hepatic steatosis, but not to ballooning degeneration or other NAFLD features. In support of this, biochemically analyzed liver lipids correlated with fetuin A in plasma ( r = 0.34, p = .033) and with hepatic fetuin A mRNA (r = 0.54, p < .001). In addition, plasma fetuin A was related to hepatic mRNA (r = 0.32, p = .036), while circulating levels were reduced by 64% with acute liver failure ( p < .001), confirming the liver as main fetuin A source. Conclusion : Fetuin A is suggested as noninvasive biomarker of hepatic steatosis in preoperative settings.